Development of non-woven nanofibers of egg albumen-poly (vinyl alcohol) blends: influence of solution properties on morphology of nanofibers - Rathna, Gundloori Venkata Naga; Jog, Jyoti Prakash; Gaikwad, A. B. (Polymer Journal, 2011)
Egg albumen (EA), a highly functional globular protein with desirable properties, is the least-explored material for biomaterial applications, although it is available in abundance. In our studies, we explored the viability of EA and various blends with biocompatible and non-toxic poly (vinyl alcohol) (PVA) to produce nanofibers for biomedical applications. EA and PVA blends were prepared in various compositions. Electrospinning was used to fabricate non-woven nanofibers. Solution properties, such as viscosity and electrical conductivity, were evaluated for various prepared solutions. Solution viscosity increased with increasing polymer concentration. Solutions with higher contents of EA recorded increased conductivity, which decreased with increasing PVA content. The influence of solution properties on the morphological appearance of as-spun products was studied using scanning electron microscopy. Instead of nanofibers, nanoparticles and microparticles of EA were produced at even higher contents. In contrast, a gradual increase in the addition of PVA content to 8% EA solution resulted in the transformation of particles from large agglomerates to very fine fibers (approximate to 100nm in diameter) because of the influence of polymer content, viscosity and conductivity. The polymer-polymer interactions in the prepared materials have been validated by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and gel electrophoresis. Polymer Journal (2011) 43, 654-661; doi:10.1038/pj.2011.34; published online 18 May 2011
Keywords: Biocompatibility; biodegradable; blends; nanotechnology; Proteins

Blends of shellac as nanofiber formulations for wound healing - Vannuruswamy, Garikapati; Rathna, Gundloori Venkata Naga; Gadgil, Bhagyashri Shashikant Thorat; Gadad, Anand Panchakshari (Journal of Bioactive and Compatible Polymers, 2015)
Shellac is being used in food, pharmaceutical, and agricultural industries. It is seldom used for biomedical applications due to its poor mechanical property and instability. We designed thermoresponsive shellac-based bioactive nanofiber mats that mimic extracellular matrix to extend their utility in wound healing. Various blend compositions of shellac, gelatin, and poly(N-isopropylacrylamide) enriched with a bioactive agent, nadifloxacin, were prepared and nanofiber mats were fabricated. The morphology of the nanofiber formation was influenced by the concentration of polymer, drug, and polymer blend composition. Polymer-drug interactions and thermal and crystalline properties of nanofiber mats were analyzed. The shellac/gelatin/poly(N-isopropylacrylamide) blend of composition 3%/7%/3% (w/v) was chosen to evaluate in vitro drug release. Release studies recorded slow, constant, and sustained release for 140h. The release kinetics and mechanism confirmed zero-order release with resultant r(2) values greater than 0.99, and the Korsmeyer-Peppas release exponent (n) was slightly higher than 0.8, which indicated that drug diffusion was anomalous or non-Fickian type and drug release followed diffusion involving chain stretching. Indirect cytotoxicity studies recorded insignificant toxicity against normal human fibroblast cells. In vivo studies demonstrated that drug-loaded nanofiber mats were more suitable for faster tissue regeneration as compared to nanofiber mats without drug and commercial nadifloxacin cream.
Keywords: drug release and mechanism; nanofibers; Shellac; thermoresponsive; tissue regeneration